Tungsten promoted ammonium and potassium ferrierite: deactivation during the skeletal isomerization of linear butenes - Finelli, Zunilda Rosa (2001)
Deactivation of tungsten promoted ferrierite during the skeletal isomerization of 1-butene at 400°C, atmospheric pressure and 0.15 atm 1-butene partial pressure was studied. Both potassium and ammonium ferrierites were impregnated with tungsten species using either tungstic acid or ammonium metatungstate as precursors, reaching loadings between 1.4 and 7.3%. After the tungsten addition on both ferrierite samples, neither the acid strength distribution nor the total acidity corresponding to the unpromoted materials change significantly. The strongest acid sites present on the ammonium ferrierite with and without tungsten and absent on the tungsten promoted potassium ferrierite, are responsible for the side-reactions. Deactivation of tungsten promoted ferrierites shows differences. Ammonium ferrierite with and without tungsten reach similar carbon contents, being larger than the ones obtained on potassium ferrierite with and without tungsten. In all cases, the carbonaceous deposit shows both olefinic and aromatic species, the proportion depending on the samples. Coke on tungsten promoted potassium ferrierite shows mainly an olefinic nature, while the deposit formed on tungsten promoted ammonium ferrierite has a more aromatic character. For the latter samples, the complete coke removal needs higher temperatures. The strength of acid sites determines not only the carbonaceous deposit amount but also its degree of condensation. The low isobutene selectivity at short time-on-stream (TOS) is avoided by starting the 1-butene feed with the catalytic bed at 200°C and then increasing temperature up to 400°C. It can be considered that a strong adsorption of reactant molecules takes place at low temperatures, thus deactivating the strongest acid sites.